TINJAUAN UNDANG-UNDANG NOMOR 16 TAHUN 2019 TERHADAP PENINGKATAN ANGKA PERKAWINAN DI BAWAH UMUR - Karina Novita Dewi (2022)
The amendment to the Marriage Law to equalize the age limit for marriage certainly has the aim of reducing underage marriage. With the age being changed to 19 years, it is felt that both parties are ready physically and psychologically. The purpose of this research is to review the Marriage Law regarding changes in the age limit whether it causes an increase in underage marriages and also about the efforts made by the government to suppress the rate of increase in underage marriages. The research method used is a normative juridical type with a problem approach using a status approach. The data was obtained using a literature collection method based on scientific journals, books and online news. These data were analyzed using qualitative techniques. The results showed that changes in the age limit for marriage caused the number of underage marriages to increase so that these changes have not been able to suppress the number of underage marriages. In addition, there are efforts that the government can take to reduce the rate of increase in underage marriages, such as education and fostering couples before marriage. The conclusion of this study is that changes in the Marriage Law regarding the age standard for marriage are not effective in the field. With these changes, which originally had the aim of reducing early marriage, it became a new problem. Thus, increasing the age limit is not a way to suppress the increase in underage marriage. Keywords: Marriage Law, Enhancement, Early Marriage